Scissor-Induced Penetrating Brain Injury in a Child: A Case Report - Surendran, Clara Meerashini; Abu Hassan, Asrarul Fikri (IIUM Medical Journal Malaysia, 2025)
Penetrating brain injury (PBI) is a rare but severe form of traumatic brain injury, especially when caused by non-missile, low-velocity objects. We report a case involving a 12-year-old boy who sustained a penetrating frontal brain injury after falling with a scissor in hand during a school activity. The scissor penetrated the right orbital roof and entered the anterior cranial fossa, injuring the right frontal lobe and causing an intraparenchymal hematoma. Computed tomography (CT) confirmed the trajectory and extent of injury. The patient underwent emergency craniotomy and foreign body removal. Postoperatively, he recovered without neurological deficits, cerebrospinal fluid (CSF) leakage, or recurrent seizures. This case highlights the importance of timely imaging, careful surgical planning, and adherence to management principles to optimize outcomes in pediatric PBI.